Ventilator associated pneumonia: bacterial agents and antibiogram at a Tertiary Care Centre in Kathmandu - Pandey, Ritu; Amatya, Ritu; Adhikari, Ram Prasad; Khanal, Laxmi Kant; Khadka, Sushila (International Journal of Infection Control, 2025)
The most common nosocomial infection seen in patients under mechanical ventilation is ventilator-associated pneumonia (VAP). This study is conducted to study rate of VAP, bacterial agents, and their antibiogram. This was a hospital based, observational cross–sectional study of all the patients who were mechanically ventilated in the intensive care unit at Nepal Medical College Teaching Hospital, Kathmandu during a period of one year. Endotracheal aspirates were processed for bacterial isolation and identification and their antibiotic susceptibility test. Significant bacterial growth was considered on the basis of significant gram stain and semi-quantitative culture obtained by endotracheal sampling. Significant bacterial growth was found in 48(57.8%) endotracheal aspirates (n = 83) of which 4(8.3%) were from cases of VAP and 44(91.7%) from Ventilator associated condition (VAC).VAP rate among patients was 4.8%. Among four VAP cases, two endotracheal aspirates grew Klebsiella pneumoniae, one grew Acinetobacter calcoaceticus baumannii complex, and one grew both Pseudomonas aeruginosa and K. pneumoniae. All isolates of K. pneumoniae were MDR and ESBL producers where two of them were AmpC β-lactamase and MBL producers. The P. aeruginosa isolated was MDR and produced AmpC beta lactamase, MBL and ESBL. The isolated Acinetobacter calcoaceticus baumannii complex was also MDR. VAP is a commonly encountered complication in mechanically ventilated patients. The MDR pathogens associated with VAP and VAC call for special attention to care for the ventilated and need for strict adherence to infection control practices including VAP bundle care.